2020
DOI: 10.1021/acs.jafc.0c01617
|View full text |Cite
|
Sign up to set email alerts
|

Cerasus humilis Cherry Polyphenol Reduces High-Fat Diet-Induced Obesity in C57BL/6 Mice by Mitigating Fat Deposition, Inflammation, and Oxidation

Abstract: This study aimed to determine the anti-obesity effects and mechanisms of Cerasus humilis polyphenol (CHP) in C57BL/6 obese mice and 3T3-L1 cells. High-performance liquid chromatography−electrospray ionization-tandem mass spectrometry was used for the qualitative and quantitative identification of CHP components. The obese mice, induced by feeding high-fat diet (HFD), were treated with CHP (250 mg/kg/day) by gavage for 12 weeks. Orlistat was gavaged at 15.6 mg/kg bw/day, as a positive control group. The analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
(91 reference statements)
1
24
1
Order By: Relevance
“…Weight loss or reduction of weight gain as an effect of iridoids [ 29 , 30 , 31 , 32 ] and anthocyanins [ 33 , 34 , 35 , 36 ] were also observed in other research models. This also applied to models in which compounds from active extract groups were tested, e.g., loganic acid [ 37 ], cyanidin [ 38 ] or pelargonidin [ 39 ]. What distinguishes our research model from quoted studies, is that it was conducted not on commonly tested rats or mice, but on rabbits–nonrodents that share much more similar lipid metabolic pathways with humans.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss or reduction of weight gain as an effect of iridoids [ 29 , 30 , 31 , 32 ] and anthocyanins [ 33 , 34 , 35 , 36 ] were also observed in other research models. This also applied to models in which compounds from active extract groups were tested, e.g., loganic acid [ 37 ], cyanidin [ 38 ] or pelargonidin [ 39 ]. What distinguishes our research model from quoted studies, is that it was conducted not on commonly tested rats or mice, but on rabbits–nonrodents that share much more similar lipid metabolic pathways with humans.…”
Section: Discussionmentioning
confidence: 99%
“…With economic development and improvement of living standards, obesity has become a major concern for global health. The hypertriglyceridemia, one of the obesity phenotypes, is becoming a risk factor for many chronic diseases . Chronic nutrient overload, especially the large amount of dietary fat, is often blamed for the leading cause of lipid metabolism disorder .…”
Section: Introductionmentioning
confidence: 99%
“…The hypertriglyceridemia, one of the obesity phenotypes, is becoming a risk factor for many chronic diseases. 1 Chronic nutrient overload, especially the large amount of dietary fat, is often blamed for the leading cause of lipid metabolism disorder. 2 However, many studies revealed that the medium-chain triglyceride (MCT) oil had health benefits because of their unique metabolic pathways in vivo.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The development of insulin resistance affects oxidative stress in diabetic mice, leading to a significant increase in the levels of reactive oxygen species (ROS) and MDA in mice ( Li et al, 2021 ). Previous studies have proven that a large number of antioxidant enzymes in organisms, such as SOD, T-AOC and GSH-PX, can suppress oxidative stress by scavenging ROS levels ( Liu S. W. et al, 2020 ; Wu et al, 2021 ). The liver is the largest metabolic organ possessing abundant antioxidant enzymes.…”
Section: Resultsmentioning
confidence: 99%